Immunotherapy of Ovarian Cancer: The Role of Checkpoint Inhibitors - Francesca De Felice; Claudia Marchetti; Innocenza Palaia; Daniela Musio; Ludovico Muzii; Vincenzo Tombolini; Pierluigi Benedetti Panici (Journal of Immunology Research)
Ovarian cancer is the most important cause of gynecological cancer-related mortality, with the majority of women presenting with advanced disease. Although surgery and chemotherapy can improve survival rates, it is necessary to integrate alternative strategies to improve the outcomes. Advances in understanding the role of immune system in the pathogenesis of cancer have led to the rapid evolvement of immunotherapy, which might establish a sustained immune system response against recurring cancer cells. Recently, it has emerged that powerful immunologic effector cells may be blocked by inhibitory regulatory pathways controlled by specific molecules often called “immune checkpoints,” which turn off the immune system. Similarly, cancer cells are able to use these checkpoints to avoid immune control and rejection. Inhibition of these inhibitory pathways represents a potent strategy in the fight against cancer and is currently under investigation with encouraging results in some cancers, such as melanoma. In ovarian cancer researches are still in an early phase, but with promising results. In this review we will explore the rationale of immunotherapy in ovarian cancer with a special focus on these emerging molecules.